تأثير زمن التخزين والتقادم بالظروف الطبيعية على التصلب ومنحنيات الامتصاصية لمركبات البولي استر غير المشبع المسلحة بالألياف الزجاجية - منصور, رامي; الحموي, لطيفة (Latakia University Journal -Engineering Sciences Series, 2016)
يهدف البحث إلى دراسة تأثير المعالجة الحرارية على تصلب البولي استر غير المشبع المسلحة بالألياف الزجاجية، ودراسة تأثير زمن التخزين وزمن التعرض للتقادم الطبيعي على منحنيات الامتصاصية. أظهرت نتائج الاختبارات صعوبة تحقيق التصلب الكامل لمادة الأساس المدروسة، وأن العينات المخزنة لمدة ثلاث سنوات تبدي مقاومة للتحلل بالماء العذب والماء المالح أكبر من العينات المخزنة لمدة ثلاثة أشهر أو المعرضة للتقادم لمدة ثلاث سنوات، كما أظهرت نتائج الاختبارات أن الامتصاصية في طبقة رقيقة جداً ولا يمكن منعها بزيادة عدد طبقات التسليح. This research aims to study the effect of heat treatment on curing of reinforced Unsaturated Polyester Resin (UPR) with fiberglass, and to study the effect of storage time and the time of exposure to natural aging on curves absorption. The results showed that it is very difficult to reach a fully curing to UPR matrix, and Storage samples for three years reveal resistance to degradation in fresh and seawater comparing with storage samples for three months, or aging by exposed to environmental for three years. The results showed also that the absorption occurs by thin film, and not prevent by increasing the layers of reinforcement